Synergistic Effect of Potassium Clavulanate in Combination withCefamandol and Ceftazidime on ï¢- Lactamase, Extracted From Resistant E.coli - Siham S. Shaokat; Hamoudi A. Hameed (College of Pharmacy University of Baghdad, 2017)
The aim of this study was to evaluate in-vitro activity of Cefamandol and Ceftazidime, in combination with potassium clavulanate against 10 uropathogenic E.coli isolated from patients with chronic complicated urinary tract infections (UTIs), these isolates were identified by the Api identification systems.The antimicrobial susceptibility tests were determined by Kirby-Bauer method and the minimum inhibitory concentrations of Cefamandol and Ceftazidime, were determined, by tube method. These isolates were resistant to Ampicillin (Amp), Amoxicillin (Amo), Carbenicillin (Cb), Ticarcillin (Tic), Amoxicillin\ Potassium Clavulanate Augmentin, (Amo\CA), Ticarcillin\ Potassium Clavulanate Timentin (Tic\CA), Cefamandol (Cfm) and Ceftazidime (Cfz), also resistant to other antibiotics, such as Tetracycline, Chloramphenicol, Trimethoprim and (50% of the isolates were resistant to Nalidixic acid and Rifampicin). Transfer of plasmids by direct conjugation experiments were performed by mating 10 strains with recipient strain E.coliK12C 600 Rif or Nal resistant, and cell free b- lactamases were prepared and detected by macro-iodometric method. The activities of each cell free bâ€" lactamases extract against Cfm and Cfz were determined by disks diffusion method (microbiological Masuda method) and by macro-iodometric method. The activity of b- lactamases was inhibited by the addition of Potassium Clavulanate. Conclusion: Good effectiveness of Cfm\ CA and Cfz\ CA was obtained against resistant strains of E.coli due to complicated urinary tract infection (UTIs). Key words: b- lactamases, Cefamandol, Ceftazidime, Timentin and Augmentin .